A TESS search for donor-star pulsations in high-mass X-ray binaries - Ramsay Gavin; Hakala Pasi; Charles Philip A. (OXFORD UNIV PRESS, 2025)
Ground-based optical photometry of the counterparts of high-mass X-ray binaries (HMXBs) has revealed the presence of periodic modulations on time-scales of similar to 0.3-0.5 d. More recent space-based observations (CoRoT and TESS) of OB and Be stars have shown that pulsations caused by p and g modes are common in early-type stars. We have therefore undertaken a systematic search for variability in the optical counterparts of 23 HMXBs (mostly neutron star systems, but including one black hole, Cyg X-1) using TESS data primarily in 2 min cadence mode. After removing the orbital period modulation in four systems, we find that all 23 sources show evidence for quasi-periodic variability on periods shorter than similar to 1 d. We compare their power spectra with those from observations of other OB- and Be-type stars. In two systems, V725 Tau and HD 249179 (which may not be an HMXB), we find evidence for an outburst, the former being simultaneous with an X-ray flare. We search for changes in the power spectra over the outburst duration and compare them with outbursts seen in other Be systems.